New current-controlled current-mode sinusoidal quadrature oscillators using CDTAs - Summart, Saksit; Thongsopa, Chanchai; Jaikla, Winai (My University, 2015)
This article presents new current-mode oscillator circuits using CDTAs which is designed from block diagram. The proposed circuits consist of three CDTAs and two grounded capacitors. The condition of oscillation can be adjusted electronically/orthogonally from the oscillation frequency by adjusting bias current of the CDTAs. The proposed quadrature oscillators have high output impedance and use only grounded capacitors without any external resistor which is very appropriate for future development into an integrated circuit. The PSPICE simulation and experimental results are corresponding to the theoretical analysis.
Keywords: CDTA; Current-mode; Quadrature oscillator